Berberine impairs coxsackievirus B3‐induced myocarditis through the inhibition of virus replication and host pro‐inflammatory response. Issue 6 (29th December 2020) - Dai, Qian; He, Xiaomei; Yu, Hua; Bai, Ying; Jiang, Lu; Sheng, Halei; Peng, Jin; Wang, Maolin; Yu, Jiang; Zhang, Kebin
Abstract: Berberine (BBR), an isoquinoline alkaloid isolated from Rhizoma coptidis, is reported to possess antiviral activity. Our previous study has shown that BBR alleviates coxsackievirus B3 (CVB3) replication in HeLa cells. However, the anti‐CVB3 activity of BBR is still unclear in vivo. In this study, we explored the effect of BBR on CVB3‐induced viral myocarditis in mice. These results demonstrated the beneficial effect of BBR on alleviating CVB3‐induced myocarditis in vivo, which sheds new light on the utility of BBR as a therapeutic strategy against CVB3‐induced viral myocarditis.